A universidade da maturidade - UMA/UFT como itinerário formativo para a pessoa idosa - Brito, Marlon Santos de Oliveira (Universidade Federal do Tocantins, 2022)
The work is linked to the Graduate Program in Education at the Federal University of Tocantins (PPGE/UFT), in the State, Society and Educational Practices line. The research aimed to investigate the University of Maturity, from the Federal University of Tocantins (UMA/UFT) as a possible Training Itinerary for the elderly person who studies Basic Education, in the form of Youth and Adult Education. For this, a documental analysis of eleven publications related to the work of Social Technology UMA/UFT was carried out, with a methodology based on the authors Marconi and Lakatos (2003), Gil (2008), Minayo (2008) and Miranda (2005). The analyzes followed the steps proposed by Bardin (2011): pre-analysis, material exploration, coding, recording units, context units, enumeration, categorization, treatment of the results obtained and interpretation by inference. The literature review addressed the authors: Arroyo (1986, 2015); Brandão (2010); Demo (2021); Faleiros (2007); Frigotto; Ciavatta and Ramos (2005); Gadotti (2003 and 2007); Julia (2001); Kuenzer (2012); Libâneo (2010); Mello (2001); Merleau-Ponty (1971 and 2012); Pacheco (2005); Saviani (2013); Villas-Boas (2016). The research revealed the contribution of the PPGE/UFT with the United Nations (UN) and other international and national entities in favor of the Decade of Healthy Aging (2021-2030); the contribution of the Sarah Gomes Intergenerational Center, from UMA/UFT, with collaborative actions that improve the lives of the elderly and the communities where they live; the materialization of political-pedagogical proposals that become effective in living school curricula and articulated with the interests of men and women who have aged. It was concluded that there is a need to continue the dialogue with the Youth and Adult Education Schools, in addition to the experiences and collaborations that allow Tocantins men and women to achieve an active and dignified aging, with school curricula that offer a return to studies, permanence and completion with quality. Therefore, the Training Itineraries must be guided by the principles of intergenerational education, with educational practices that reach the subjectivity of the elderly. After all, in the 21st century, men and women live longer, are active, connected, feel, want and have the subjective right to learn.